Introducing a Model for Customer Satisfaction Based Smart Business Systems - Lotfi, Farhad; Mansourifard, Mehdi (E-business technologies conference proceedings, 2021)
In the current era, with the growth of ICT, business systems experience a new form. Due to the variety of products and changing people’s tastes, online sales services and platforms should be developed to achieve satisfaction. On the other hand, with the increasing expansion of data in the online business context, the variety of new products, and changing people’s tastes, there is a need to run online businesses on a smart platform. This study believes that providing some solutions to the fundamental gaps in online businesses can increase customer satisfaction. In the model prepared in this research, basic factors such as Real-Time Responsiveness are addressed. Thus, more detailed attention has been paid to people’s tastes compared to previous studies so that the product offer would seem closer to the people’s tastes. As a result, in this study, we tried to prepare an electronic business model based on smart platform to increase the quality of services, achieve satisfaction and establish electronic customer loyalty.